2020
DOI: 10.30935/ejmets/8299
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Reserve Food During COVID-19 Pandemic Among Bangladeshi Internet Users: Based on Theory of Planned Behaviour

Abstract: Introduction:The COVID-19 is probably the most terrible pandemic in the world, because there is no approved vaccine or treatment for this rapidly spreading disease. Most of the country is locked down for reducing spreading disease. Due to lockdown situations people are afraid and confused for getting basic food available at hand. Objective:The purpose of this study is to investigate the expanded theory of planned behaviour model and adding risk perception variables for intention to reserve food during covid-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…2.3.5 Perceived behavioral control. Khan (2020) and Long and Khoi (2020) revealed that the pandemic situation might incite customers to procure more reserve goods and services. This is a result of high customer risk perception and high-risk awareness of the pandemic.…”
Section: Subjective Normsmentioning
confidence: 99%
“…2.3.5 Perceived behavioral control. Khan (2020) and Long and Khoi (2020) revealed that the pandemic situation might incite customers to procure more reserve goods and services. This is a result of high customer risk perception and high-risk awareness of the pandemic.…”
Section: Subjective Normsmentioning
confidence: 99%
“…People have been afraid to come out of their homes because COVID-19 has changed societal norms across the world. According to Khan (2020), the severity risks of COVID-19 have enhanced online shopping behavior. Hence, this study hypothesizes as follows:…”
Section: Severity Riskmentioning
confidence: 99%
“…Other studies investigated whether consumers' food shopping behavior and demand have been affected by the COVID-19 related lockdown. For instance, Long and Huy Khoi (2020) and Khan (2020) adopted the Theory of Planned Behavior model (TPB) in combination with the theory of consumer risk perception to understand the factors that affect the hoarding food behavior of Vietnamese and Bangladeshi consumers during COVID-19 pandemic. The results from these studies indicate that the risk perception of the COVID-19 pandemic has positively affected consumer attitudes towards the intention to hoard the food.…”
Section: Introductionmentioning
confidence: 99%